Die räumliche Sprache der Erfahrung. Die innere Zeit und der innere Raum - Molchanov, Viktor (Investigaciones Fenomenológicas, 2021)
This investigation addresses the internal experience as a spatial phenomenon. Ascertaining the difference between internal and external experience as a space metaphor leads to the question of the source of the space metaphors in principle. The analogy between time and space and the space metaphors in Husserl’s conception of time are considered. The question of the temporality of consciousness, evidence, and internal experience are brought to the fore by comparing Brentano’s and Husserl’s conceptions. The difference between the direct and indirect modes of consciousness by Brentano, his conception of time as the boundary in the continuum, and his concept of the proteraesthesis proves to be relevant for the concept of internal experience as a spatial phenomenon. The essay calls in question the self-sufficiency of time-experience and the traditional correspondence of time to the internal experience and of space to the external one. The relation of the Here/There- and Now/Then-experience is discussed. I intend to elucidate the experience of boundary as a primary internal experience from which the space-experience arises. In its turn the boundary-consciousness has its origin in the differentiation-experience. In the latter there is no time, the internal one included, but there is a boundary-experience as a primary and indirect experience. Time is s shadow of space; it originates from the manifold of human spaces. Esta investigación aborda la experiencia interna como un fenómeno espacial. Determinar la diferencia entre la experiencia interna y externa como una metáfora del espacio conduce a la cuestión de la fuente de las, en principio, metáforas espaciales. Aquí se atiende la analogía entre el tiempo y el espacio y las metáforas espaciales en la concepción del tiempo de Husserl. Se ponen de relieve la cuestión de la temporalidad de la conciencia, la evidencia y la experiencia interna, comparando las concepciones de Brentano y Husserl. La diferencia entre los modos de conciencia directos e indirectos de Brentano, su concepción del tiempo como el límite en el continuo, y su concepto de la proteroestesis, son relevantes para el concepto de experiencia interna como un fenómeno espacial. El ensayo cuestiona la autosuficiencia de la experiencia del tiempo y la correspondencia tradicional del tiempo con la experiencia interna y del espacio con la externa. Se discute la relación de la experiencia Aquí/Ahí y de la experiencia Ahora/Luego. Mi in-tención es esclarecer la experiencia de la frontera como una experiencia interna primaria de la cual surge la experiencia espacial. A su vez, la con-ciencia de frontera tiene su origen en la experiencia de diferenciación. En esta último no hay tiempo —incluso el interno—, pero hay una experiencia límite como experiencia primaria e indi-recta. El tiempo es la sombra del espacio; se origina en la multiplicidad de espacios humanos. .